X-shaped structure of bacterial heterotetrameric tRNA synthetase suggests cryptic prokaryote functions and a rationale for synthetase classifications. Issue 17 (14th August 2021) - Ju, Yingchen; Han, Lu; Chen, Bingyi; Luo, Zhiteng; Gu, Qiong; Xu, Jun; Yang, Xiang-Lei; Schimmel, Paul; Zhou, Huihao
Abstract: AaRSs (aminoacyl-tRNA synthetases) group into two ten-member classes throughout evolution, with unique active site architectures defining each class. Most are monomers or homodimers but, for no apparent reason, many bacterial GlyRSs are heterotetramers consisting of two catalytic α-subunits and two tRNA-binding β-subunits. The heterotetrameric GlyRS from Escherichia coli ( Ec GlyRS) was historically tested whether its α- and β-polypeptides, which are encoded by a single mRNA with a gap of three in-frame codons, are replaceable by a single chain. Here, an unprecedented X-shaped structure of Ec GlyRS shows wide separation of the abutting chain termini seen in the coding sequences, suggesting strong pressure to avoid a single polypeptide format. The structure of the five-domain β-subunit is unique across all aaRSs in current databases, and structural analyses suggest these domains play different functions on α-subunit binding, ATP coordination and tRNA recognition. Moreover, the X-shaped architecture of Ec GlyRS largely fits with a model for how two classes of tRNA synthetases arose, according to whether enzymes from opposite classes can simultaneously co-dock onto separate faces of the same tRNA acceptor stem. While heterotetrameric GlyRS remains the last structurally uncharacterized member of aaRSs, our study contributes to a better understanding of this ancient and essential enzyme family.